Six core values in natural law as a common concern for human development - Usman Quddus; Dennis W. K. Khong (Cogent Social Sciences, 2023)
This paper attempts to identify the core values in natural law as a shared value system, based on natural law theories and issues confronting the world today. It identifies the doctrines that influence major natural law thinking and then proposes a minimum content for constitutionalism based on such natural law shared values. The purpose is to identify with clarity over-riding principles of natural justice in solving practical problems. The methodology adopted is doctrinal, conceptual, and analytical. The findings detail common values for humanity and mandate revisions of modern constitutions considering the conclusions reached based on natural law dictums. This article is the first of its kind to link natural law with constitutionalism while explicating the ends of natural law considering experience and observation. It is also proposed in this research that if governments fail to meet the social contract with the people on the core values, then international dispute resolution forums and human rights advocates should play their part in enforcing these common core values.